Sistem Pendukung Keputusan Metode Electree Dalam Pemilihan Dosen Terbaik Pembelajaran Pada Fakultas Teknik Dan komputer - Yunita Sari Siregar; Herlina Harahap; Boni Oktaviana Sembiring; Nenna Irsa Syahputri; Divi Handoko (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2022)
Lecturers are professional educators who have a role to develop, transform and disseminate knowledge in higher education. At the Faculty of Engineering and Computers, the process of selecting the best lecturers in learning for students in the class will be carried out with the assessment criteria being discipline, material, attitudes and learning techniques. The method used is a decision support system, the Electre method. Electree is a method that produces a ranking in which several steps are performed, namely normalizing the decision matrix, weighting the matrix, determining the concordance and discordance set, calculating the concordance and discordance matrices, determining the dominant matrix, determining the aggregate dominant matrix and alternative elimination. Based on the results of tests that have been carried out using the electree method, the 10 best lecturers' test data resulted in an accuracy value of 60% and the 3 highest ranking scores for lecturer 7, lecturer 5 and lecturer 1. Keywords:   Decision Support System, Electre, Lecturer, Learning, Faculty of Engineering and  Computers